PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL PERSPEKTIF HUKUM ISLAM (STUDI KASUS DI POLRES PALOPO) - Husnawati (Datuk Sulaiman Law Review (DaLRev), 2023)
This research discusses about defamation through social media from the perspective of Islamic law. The purpose of this research to know and understand the process of occurrence of defamation events through social media and to know and understand the views of Islamic law on defamation through social media. The type of research used is empirical legal research with a case study research approach. Data collection techniques were carried out by interview, observation and documentation. After all the data is collected, then the data is analyzed by reduction and display so that it is drawn or gets the results research that answers the problem of this research. The results of this study show the process of defamation events through social media at the Palopo City Police, namely: the occurrence of defamation through social media at the Palopo City Police Station, which is one of the events that occurred in South Wara Palopo City carried out by the initials WS where WS through his social media facebook on Thursday 13 January 2022, around 15:00 in Wara Selatan Palopo City posted or displayed a photo of the complainant on social media, while writing the name of the complainant by saying that the complainant had an affair with the perpetrator's husband by also saying I was the whistleblower. the post I feel ashamed and report the incident. Legal certainty related to defamation on social media, namely Law no. 19 of 2016 on the amendment of Law no. 11 of 2008 ITE is contained in article 27 paragraph 3 and is subject to sanctions in article 45 paragraph 3. And according to Islamic law, defamation is included in the category of jarimah ta'zir, namely a crime against the honor and good name of a person so that it can bring down that person's dignity. In giving punishment to perpetrators of defamation through social media, the judge in this case is given the authority to impose penalties for the perpetrators of Jarimah ta'zir by considering the laws in force in Indonesia, namely Law Number 19 of 2016 on the amendment of Law Number 11 of 2008 ITE information and electronic transactions.